Small beneficial effect of caffeinated energy drink ingestion on strength - Collier, N. B.; Hardy, M. A.; Millard-Stafford, M. L.; Warren, G. L. (The Journal of Strength and Conditioning Research, 2016)
Because caffeine ingestion has been found to increase muscle strength, our aim was to determine whether caffeine when combined with other potential ergogenic ingredients, such as those in commercial energy drinks, would have a similar effect. Fifteen young healthy subjects were used in a double-blind, repeated-measures experimental design. Each subject performed 3 trials, ingesting either a caffeinated energy drink, an uncaffeinated version of the drink, or a placebo drink. The interpolated twitch procedure was used to assess maximum voluntary isometric contraction (MVIC) strength, electrically evoked strength, and percent muscle activation during MVIC of the knee extensors both before and after drink ingestion, and after a fatiguing bout of contractions; electromyographic (EMG) amplitude of the knee extensors during MVIC was also assessed. The mean (±SE) change in MVIC strength from before to after drink ingestion was significantly greater for the caffeinated energy drink compared with placebo [+5.0 (±1.7) vs. -0.5 (±1.5)%] and the difference between the drinks remained after fatigue (p = 0.015); the strength changes for the uncaffeinated energy drink were not significantly different from those of the other 2 drinks at any time. There was no significant effect of drink type on the changes in electrically evoked strength, percent muscle activation, and EMG from before to after drink ingestion. This study indicates that a caffeinated energy drink can increase MVIC strength but the effect is modest and the strength increase cannot be attributed to increased muscle activation. Whether the efficacy of energy drinks can be attributed solely to caffeine remains unclear.